The caves of the great hunters - Baumann, Hans 1914- (Pantheon Books, 1954)
Describes the discoveries and dramatic drawings of Europe's prehistoric caves--Lascaux, Altamira, Pindal, El Castillo, Niaux, Valltorta Gorge and the Gasulla Gorge.